Sistem Pakar Buta Warna Menggunakan Bangun Ruang Berbasis Mobile Dengan Sistem Operasi Android - I Wayan Putu Sarwe Windusara Windusara; Ario Yudo Husodo; Ariyan Zubaidi (Journal of Computer Science and Informatics Engineering (J-Cosine), 2018)
Color blindness is one of eye diseases that attack the eye's conical cells and making it difficult to see several colors. One way to detect color blindness in a person is using the Ishihara Test, in this test using the figure images that have any colors that can outwit the color blind. By using numbers in the Ishihara test can’t yet include some groups who can’t read the numbers, so that a new drawing is made of 2D shape that will be combined with an expert system in order to provide an initial diagnosis according to the expert. Expert systems lately can be developed on many devices, the most commonly used is a mobile application with the most popular Android operating system. In this research, there are several tests on the subject of partial color blindness and subject with a normal eye, with the result of Ishihara’s Test can reach 100% System with time limit only 15 seconds. Therefore this system has the fit of workflow and conclusion with Ishihara Test.